E-COMMERCE CUSTOM MADE SANDAL WANITA - Dewi Ratna Sari; Boni Oktaviana Sembiring; Eka Rahayu (Universitas Methodist Indonesia, 2022)
The improvement of web innovation permits individuals to acquire data rapidly and precisely. Apart from being a source of information, the internet is also used for purchasing and selling goods, a practice known as e-commerce. Yolanda is a handmade company that sells high-heeled sandals to women.The ordering process is always done through WhatsApp or in person.The goal of this research is to create an e-commerce system for custom-made women's sandals. The development of this system follows the waterfall method. The study's findings include an e-commerce system for custom-made women's sandals, which can aid in the promotion, buying, and selling of women's sandals.